Analisis Kesuksesan Sistem Informasi Keuangan Daerah dengan Mengadopsi Model DeLone & McLean - Prameswara, I Gusti Agung Bagus Putra; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 24 No 1 (2018)DO - 10.24843/EJA.2018.v24.i01.p08, 2018)
The success of an accounting information system in managing regional finances in government agencies is very important to note. Especially if there is a transition phenomenon of use from one system to another system. Success or failure of the system used can affect the performance of employees in these agencies. The purpose of this study was to assess the success of the use of the Regional Financial Management Information System (SIPKD) using the DeLone & McLean Model (2003). The research was conducted in the Secretariat of the Regional Finance Division of Denpasar City. This research takes sample based on non probability sampling method with saturated sample technique. Technical analysis used is partial least square analysis. The results of the analysis found that there were significant effects between variables on system usage, system usage on individual performance, and user satisfaction on individual performance. The level of system success measured at the level of effectiveness found results that the implementation of SIPKD in the Secretariat of the Regional Finance Division of Denpasar has been successful. Keywords: DeLone & McLean Model, SIPKD, SIA Success, Individual Performance